Disturbances in lipid second messengers generation by stimulated blood lymphocytes in breast cancer - Lazyan, M.P.; Davtyan, H.H.; Batikyan, T.B.; Kazaryan, R.A.; Alexanyan, K.A.; Galstyan, H.M.; Tadevosyan, Yu.V. (Вiopolymers and Cell, 2011)
Aim. The main objective of thisstudy wasthe comparative investigation of diverse lipid second messenger(LSM)
generation by human peripheral blood lymphocytes (HPBL) at different (5, 10, 30 and 60 s) time points of cell
co-stimulation by anti-CD3 and anti-CD28 monoclonal antibodies in norm and breast cancer (BC). Methods.
Ficoll-Hypaque gradient centrifugation. Results. The data obtained indicate that some mechanisms of LSM generation/utilization in stimulated crude HPBL were significantly altered in BC compared to norm. Particularly,
the reliable generation of arachidonyl-1,2-diacylglycerol (1,2-DAG) at the initial step (5 s) of cell stimulation
observed in norm was depressed in BC and reached the value below the basal level in unstimulated cells. It is
important that the disturbances in 1,2-DAG formation in HPBL obtained from patients with BC were identical
with those observed earlier in other forms of cancer. Conclusions. We conclude that the regularities revealed
are common characteristics for all the types of malignancy studied and can be used as additional testing parameters for cancer definition and individual correction of the chemotherapy programs for disease treatment.
Keywords: blood lymphocytes, lipid second messengers, breast cancer. Мета. Основна мета даного дослідження полягала у порівняльному аналізі процесів генерації різних ліпідних вторинних посередників (ЛВП) у загальній масі лімфоцитів периферичної крові
людини (ЛПКЛ) на різних етапах (5, 10, 30 и 60 с) костимуляції
клітин анти-CD3 і анти-CD28 моноклональними антитілами за
норми і при раку молочної залози (РМЗ). Методи. Ficoll-Hypaque
градієнтне центрифугування. Результати. Отримані дані свідчать про наявність значних порушень у механізмах утворення/
утилізації ЛВП у стимульованих ЛПКЛ при РМЗ порівняно з нормою. Зокрема, достовірна генерація арахідоніл-1,2-діацил-гліцерину (1,2-ДАГ), що спостерігається за норми, на початковому
етапі (5 с) костимуляції клітин виявилася пригніченою при РМЗ
та нижчою за контрольний рівень у нестимульованих клітинах. Треба відмітити, що порушення в утворенні 1,2- ДАГ ЛПКЛ,
одержаних від пацієнтів з РМЗ, були ідентичними з виявленими
нами раніше при інших формах ракових новоутворень. Висновки. Таким чином, можна зробити висновок, що знайдені закономірності є загальними характеристиками для всіх типів вивчених нами злоякісних пухлин і можуть бути використані як додаткові тест-параметри для виявлення раку та індивідуальної
корекції курсу хіміотерапії при лікуванні захворювання.
Ключові слова: лімфоцити крові, ліпідні вторинні посередники, рак молочної залози. Цель. Основной целью данного исследования был сравнительный
анализ процессов генерации различных липидных вторичных посредников (ЛВП) в общей массе лимфоцитов периферической крови человека (ЛПКЧ) на различных этапах (5, 10, 30 и 60 с) костимуляции клеток анти-CD3 и анти-CD28 моноклональными
антителами в норме и при раке молочной железы (РМЖ). Методы. Ficoll-Hypaque градиентное центрифугирование. Результаты. Полученные данные свидетельствуют о наличии значительных нарушений в механизмах образования/утилизации ЛВП в стимулированных ЛПКЧ при РМЖ по сравнению с нормой. В частности, наблюдаемая в норме достоверная генерация арахидонил-1,2-
диацилглицерина (1,2-ДАГ) на начальном этапе (5 с) костимуляции клеток была подавленной при РМЖ и находилась ниже контрольного уровня в нестимулированных клетках. Примечательно,
что нарушения в образовании 1,2-ДАГ ЛПКЧ, полученных от пациентов с РМЖ, были идентичны с ранее выявленными нами при
других формах раковых новообразований. Выводы. Таким образом, можно заключить, что обнаруженные закономерности являются общими характеристиками для всех типов изученных
нами злокачественных опухолей и могут быть использованы в
качестве дополнительных тест-параметров для выявления рака
и индивидуальной коррекции курса химиотерапии при лечении заболевания.
Ключевые слова: лимфоциты крови, липидные вторичные посредники, рак молочной железы.